2021
DOI: 10.1080/15205436.2021.1934702
|View full text |Cite
|
Sign up to set email alerts
|

“The Good, the Bad, and the Ugly”: A Panel Study on the Reciprocal Effects of Negative, Dirty, and Positive Campaigning on Political Distrust

Abstract: Negative campaigning is a central concept in political communication research. However, most conceptualizations of the term are rather broad, summarizing all kinds of negativity such as substantial criticism and offensive behaviors. In this paper, we distinguish negative, dirty, and positive campaigning. While negative campaigning refers to critical, civil, and non-disrespectful arguments, dirty campaigning, by contrast, is defined as "below-thebelt" attacks including incivility and unfair campaign methods. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
4
0
2
Order By: Relevance
“…Our definition of negative campaigning is broad and encompasses any attacks on party/ leader performance and traits. However, research suggests that dirty campaigning using defamatory and disrespectful comments is disliked more than informative and civil negative campaigning (Reiter & Matthes, 2021). Do different attacks affect the target party's performance differently?…”
Section: Discussionmentioning
confidence: 99%
“…Our definition of negative campaigning is broad and encompasses any attacks on party/ leader performance and traits. However, research suggests that dirty campaigning using defamatory and disrespectful comments is disliked more than informative and civil negative campaigning (Reiter & Matthes, 2021). Do different attacks affect the target party's performance differently?…”
Section: Discussionmentioning
confidence: 99%
“…To measure perceived dirty campaigning by the least favorite party, we created a filter variable asking the participants about their least favorite party in the German Bundestag, followed by two items to assess their perception of dirty campaigning by the selected party (items based on Reiter & Matthes, 2021): "The [FILTER PARTY] is disrespectful to other parties"; "The [FILTER PARTY] uses deceitful campaign techniques, for instance illegal campaign financing." We then computed a new variable consisting of that mean value per participant.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research demonstrated that uncivil campaigning and deceitful campaign techniques tend to have more negative than positive implications for democratic quality (Walter, 2021). Uncivil campaigning can decrease trust in politicians, congress, and government, as well as political participation intentions and policy support (Fridkin & Kenney, 2019;Mutz, 2015;Otto et al, 2020;Reiter & Matthes, 2021;Van 't Riet & Van Stekelenburg, 2021). Deceitful campaign techniques can decrease positive evaluations and voting intentions toward the sponsor, as well as decrease trust in politicians and trust in democracy (Vivyan et al, 2012;Von Sikorski et al, 2020).…”
Section: A Basic Conceptualization Of Dirty Campaigningmentioning
confidence: 99%
“…Ilyen megkülönböztetés lehet például tartalmi alapon az issue és a személyes típusú üzenetek vizsgálata (K. L. Fridkin & Kenney, 2011a;, melyek kapcsán elmondható, hogy utóbbiakkal szemben a választók általában kritikusabbak. Több kutató (Brooks & Geer, 2007;Mutz & Reeves, 2005;Reiter & Matthes, 2021;Sobieraj & Berry, 2011) emellett a negatív kampányon belül megkülönbözteti az ún. uncivil üzeneteket, amelyek alatt olyan megfogalmazásokat értenek, amelyek "az ellenfelet vagy politikáját kifejezetten durva, sértő vagy pejoratív jelzőkkel írja le" (K. L. Fridkin & Kenney, 2011a, o.…”
Section: A Negatív Kampány Definíciójaunclassified
“…A negatív kampány alkalmazásának legnagyobb hátránya, hogy a választók alapvetően elutasítóak az ilyen típusú üzenetekkel szemben, etikátlannak, megtévesztőnek tartják őket, különösen a személyes jellemzőkre és a magánéletre vonatkozó üzeneteket (Brooks & Geer, 2007;K. L. Fridkin & Kenney, 2008;Garramone, 1984;Johnson-Cartee & Copeland, 1989;Mutz & Reeves, 2005;Pinkleton, 1997;Reiter & Matthes, 2021). Garramone (1984) Ennek megfelelően a fejezetben a statikus magyarázatok bemutatása után a negatív kampány alkalmazásának lehetséges dinamikus magyarázatait mutatom be.…”
Section: A Bumeránghatásunclassified